Parkinson's disease cybrids, differentiated or undifferentiated, maintain morphological and biochemical phenotypes different from those of control cybrids. Issue 7 (7th May 2013) - Appukuttan, T.A.; Ali, N.; Varghese, M.; Singh, A.; Tripathy, D.; Padmakumar, M.; Gangopadhyay, P.K.; Mohanakumar, K.P.
<x xml:space="preserve">Abstract</x> SH‐SY5Y, control, and Parkinson's disease (PD) cybrids prepared from an Indian population were differentiated using retinoic acid (RA) for understanding their dopaminergic characteristics and neuritogenesis. Undifferentiated control and PD cybrids exhibited higher levels of TH mRNA, but lower c‐RET expression, short neurites, low neuritic density, and low proportion of cells with neurites compared with the undifferentiated parent cell line, SH‐SY5Y. The expression levels of DAT and Ptx3 were similar to SH‐SY5Y. PD cybrids showed poor viability and lower differentiating potency than SH‐SY5Y or control cybrids. RA treatment for 6 days elevated c‐RET expression and corrected the neuritic morphology of the control, but not of PD cybrids. Cell viability was found to be reduced in differentiated control and PD cybrids. TH expression level was significantly elevated in SH‐SY5Y following RA treatment, but not in both the cybrids. In differentiated control and PD cybrids, the TH immunofluorescence intensity was significantly lower compared with SH‐SY5Y cells. MitoTracker Green fluorescence intensity of the mitochondria was higher in differentiated PD cybrids. Dopamine released into the medium was unaffected in the differentiated SH‐SY5Y or in the control cybrids but was significantly elevated in PD cybrids. These results suggest that PD cybrids, differentiated or undifferentiated, maintained morphological and biochemical phenotypes significantly different from those of the control cybrids, or the differentiated SH‐SY5Y cells, and therefore could be an ideal cellular model of the disease for pharmacological screening of drugs and for investigation of the pathophysiology of PD. © 2013 Wiley Periodicals, Inc.